Future Ultrasound Biomarkers for Sarcopenia: Elastography, Contrast-Enhanced Ultrasound, and Speed of Sound Ultrasound Imaging - Ivanoski, Slavcho; Vasilevska Nikodinovska, Violeta (Seminars in Musculoskeletal Radiology, 2020)
Sarcopenia is the advanced and generalized loss of muscle mass and strength among the elderly population and is a cause of adverse outcomes. Methods used for the diagnosis of sarcopenia are either unavailable or expensive in everyday clinical settings. Ultrasound presents an inexpensive, convenient, and available method that offers advantages for the evaluation of skeletal muscle. Muscle quality will probably be the most important factor in defining sarcopenia in the future. Different features of muscle quality, including muscle elasticity, microcirculation and muscle perfusion during rest and physical activity, and the content of intramuscular adipose tissue can be measured using emerging and promising ultrasound techniques such as elastography, contrast-enhanced imaging, and speed of sound ultrasound technology. This article reviews the recent evidence on the use of ultrasound techniques in the assessment of muscle quality and the possibilities for the future evaluation of sarcopenia.
Keywords: sarcopenia; elastography; contrast; speed of sound